Análise do Programa de Capacitação e Aperfeiçoamento dos Servidores Técnico-Administrativos da UFC na perspectiva dos técnicos e gestores - Nascimento, Telma Araújo do (2015)
From the 1990s there have been great efforts of the publica dministration to professionalize and modernize the Brazilian public sector by modifying its operations in society. The human resources policy in the area of training is essential to redesign a new public servant’s profile, and its goal is to qualify this public servant’s performance in providing services to society. This study aimed to analyze the perceptions and impacts of training policy and professional development of technical and administrative staff of the UFC on the campus of Fortaleza, after nine years of implementation of the Positions and Career Plan of Technical and Administrative Staff (PCCTAE is the acronym in Portuguese), in view of the technical and management staff of the institution. Toachieve this purpose there were outlined the following specific objectives: to identify the profile of the public servants who attended the trainings, in view of the survey of training needs applied annually, and observe whether - in the manager's and the technical and administrative staff perspectives - the training processes have improved work routines and job performance of staff, portraying its major educational changes in the area of training and improvement. The guiding methodology of this study is based on exploratory research through a case study as a way to learn and understand the particularities and complexities of reality. The public servants’ opinions, perceptions and information were classified and analysed, which allowed a translation of them into numbers - a qualitative and quantitative approach. Data collection was by means of a questionnaire, which was applied using Google Drive tool. For entering data, it was used the Microsoft Excel program. Some results show that PCCTAE brought significant repercussions and advances in the training and professional development. It was formally recognized the public servants’ need for a continuous training for his/herlabor improvement. Incentives for training and qualification in formal education area - at the undergraduate level, specialization, master's and doctorate, with financial incentives, guaranteed by law for all classes and levels - were relevant to improve performance. Although there is still the need of the law enforcement related to the preparation of the Career Institutional Development Plan (PDIC, the acronym in Portuguese). This plan would deal with the design of institutional personnel needs, defining spaces allocation models covering each reality of the institution, training program and improvement and performance assessment program. It was observed that although legislation represents significant gains in improving the technical public servants, there wasn’t much progress in terms of career, because it allowed the rise in office itself (the training level change), and not the change of the position (job promotion) . A negative effect cited by public servants of the technical class E level refers to the wage recovery, which did not recognize all their qualifying titles during the implementation of the plan. The analyzes showed that the training program and professional development of the UFC has met the personal and professional expectations of the technical and administrative staff, making it possible to them to betterknow the academic and administrative dynamics of the institution, and therefore, making them more skilled or qualified for the performance of work activities.